1961
DOI: 10.1177/000331976101200606
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Application of Vasodilatators in Acute Coronary Occlusion

Abstract: Although 100 years has elapsed since the introduction of the nitrates and nitrites for the treatment of angina pectoris and coronary insufficiency, they are still not recommended for therapy, in the events following an actual coronary occlusion .1-4 The fact that these chemical compounds were found to be superbly effective agents for relief of the complex physiologic syndrome of angina pectoris long before its basic mechanisms were partially known or investigated is not unusual in the annals of medical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1978
1978

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Early investigators [Wiggers and Green, 1936;Zolland Norman, 1952;Kattus el a!., 1959] showed that a variety of drugs including papaverine, sodium nitrite and nitroglycerine had little effect on the collateral circulation. Hedges et al [1961] demonstrated in a small group of dogs that isosorbide dinitrate, when administered after total ligation of the circumflex artery, increased survival from 43% in controls to 100% in the experimentáis. Slejeskog et al [1963], however, showed that isosorbide dinitrate was not effective in the treatment of acute coronary artery ligation in the baboon due to the systemic hypotension caused by the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigators [Wiggers and Green, 1936;Zolland Norman, 1952;Kattus el a!., 1959] showed that a variety of drugs including papaverine, sodium nitrite and nitroglycerine had little effect on the collateral circulation. Hedges et al [1961] demonstrated in a small group of dogs that isosorbide dinitrate, when administered after total ligation of the circumflex artery, increased survival from 43% in controls to 100% in the experimentáis. Slejeskog et al [1963], however, showed that isosorbide dinitrate was not effective in the treatment of acute coronary artery ligation in the baboon due to the systemic hypotension caused by the drug.…”
Section: Introductionmentioning
confidence: 99%